BEYOND NATIONHOOD: HAUL MUSIC FROM A POSTCOLONIAL PERSPECTIVE IN WESTERN SAHARA AND MAURITANIA - Amoros, Luis Gimenez (International Library of African Music, 2020)
This article examines the mobility of a precolonial musical style known as Haul music in two African countries, Western Sahara and Mauritania. Haul music is based on a modal system in which music and poetry are intrinsically related. This article traces the historical and musicological aspects of the Haul modal system in Western Sahara and Mauritania by offering an insight into how the postcolonial period has determined two narratives of Haul: a historical nationalism by way of revitalising the precolonial past in Mauritania; and political nationalism when reconsidering the ongoing process of decolonisation in Western Sahara and the exile of its people to the refugee camps of the Hamada desert since 1975. Further, this article shows how the mobility of the Haul modal system provides a reconsideration of a precolonial past in existing music cultures in North Africa.
Keywords: Nationalism; Postcolonialism; Decolonisation; Western Sahara; Mauritania; Nationhood; Precolonial Past; Haul Music; Mobility; Trab el Bidan; Postcolonial Studies; African Music